Oxidative Stress Upregulates PDCD4 Expression in Patients with Gastric Cancer via miR-21 - Tu, Honglei; Sun, Haibing; Lin, Yan; Ding, Jie; Nan, Kejun; Li, Zongfang; Shen, Qiang; Wei, Yongchang (Current Pharmaceutical Design, 2014)
Reactive oxygen species (ROS) plays a key role in carcinogenesis by aberrantly inducing signaling networks that initiatiate tumorigenesis and stimulate tumor progression. MicroRNAs (miRNAs) comprise a novel class of endogenous, small, noncoding RNAs that negatively regulate approximately 30% of the genes in a cell via degradation or translational inhibition of their target mRNAs. However, the effects of ROS on miRNAs expression and the role of miRNAs in ROS-mediated injury on carcinogenesis are uncertain. Using UV spectrophotometry and enzyme-linked immunosorbent assay (ELISA), we examined tissues from human gastric cancers and tissues adjascent to gastric cancer and normal gastric tissues and found that total anti-oxidation competence (T-AOC), superoxide dismutase (SOD) and catalase (CAT) concentrations were lower in gastric cancer patients compared to the control subjects, while the concentrations of DNA oxidative damage product 8-oxo-deoxyguanosine (8-OHdG) was higher. To determine the potential role of miRNA in gastric carcinogenesis, real-time quantitative polymerase chain reaction (QPCR) analysis was performed. We found that human 8-oxoguanine DNA N-glycosylase 1 (hOGG1) mRNA and miR-21 expression were significantly upregulated in gastric cancer tissues than in the adjacent normal gastric tissues. Furthermore, the expression of programmed cell death 4 protein (PDCD4) in gastric cancer tissues was significantly lower than in adjacent normal gastric tissues. The expression of miR-21 and PDCD4 was highly correlated with the degree of differentiation, tumor staging, local lymphatic node metastasis and remote metastasis. Expression of miR-21 was negatively correlated with T-AOC, SOD and CAT, but positively correlated with 8-OHdG and hOGG1mRNA. In addition, the relative expression of PDCD4 was negatively correlated with miR-21. These results suggest that the defensive balance of oxidation and antioxidant system in patients with GC was impaired, resulting in enhanced oxidative tissue injury, which may directly contribute to gastric carcinogenesis. Thus we conclude that ROS promotes gastric carcinogenesis via upregulating miR-21 expression which in turn down-regulates the expression of PDCD4 in gastric cancer cells.
Keywords: Oxidative stress